Facilitating written work using computer word processing and word prediction. - Handley-More D; Deitz J; Billingsley FF; Coggins TE (American Journal of Occupational Therapy)
OBJECTIVE: The purpose of this study was to investigate whether occupational therapy intervention that focused on teaching children to use word processing, either alone or with word prediction, was effective in improving the written communication skills of children with learning disabilities and handwriting problems. METHOD: A single-subject alternating treatments design was replicated across three children in grades 4 and 5. During the baseline phase the children wrote stories by hand; during the intervention phase, the children wrote stories, alternating among handwriting, word processing, and word processing with word prediction. Dependent variables focused on percentages of legible words, percentages of correctly spelled words, total amount written, and rate of writing. Data were analyzed by visual inspection. RESULTS: Results were variable. Two children had clear improvements in legibility when using either word processing alone or with word prediction. These same children demonstrated clear improvements in spelling when using word prediction. Though rate of writing was best for two children when using handwriting, relative to total amount produced, one method was not clearly preferable to another. CONCLUSION: Occupational therapy intervention involving word processing with word prediction improves the legibility and spelling of written assignments completed by some children with learning disabilities and handwriting difficulties. It is important to evaluate each child individually and provide training and ongoing support for technology use.